The Power of Art - Lewis, Richard L.; Lewis, Susan Ingalls 1949- (Wadsworth Cengage Learning, 2014)
"Compelling, comprehensive, and accessible, Lewis and Lewis's The Power of Art, 3rd Edition, features an exciting new layout and gorgeous images -- all designed to connect with today's student. Instructors and students continue to praise the engaging, conversational writing style that makes it easier for students to both understand and enjoy reading the material. The Power of Art delivers a brief, yet comprehensive survey, demonstrating that art is everywhere and relevant to all students -- no matter what their majors happen to be. The text incorporates global material throughout to demonstrate cultural intersections and mutual influences. "Art News" boxes present real events that connect art to students' lives. In addition to excellent art history coverage, The Power of Art features a diverse mix of artists and spotlights the latest technologies used to create art. Digital resources that accompany the book make it easier for students to learn and study the material. The set includes image flashcards, Foundations Interactive Modules, videos, quizzes, an interactive book, and more. With the best price in the market, The Power of Art delivers unrivaled value for instructors and students alike."--Publisher's description.